WOMEN SELF-IMAGE ON JI SUN WOO'S CHARACTER IN KOREAN DRAMA ”THE WORLD OF THE MARRIED” - Josephine Elvira; Dwi Setyo Riani; Irma Rasita Gloria Barus; Ira Resmayasari (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
Korean dramas are very popular with audiences from various mass media and social media. With a very interesting storyline, it is able to hypnotize Indonesian audiences to become active viewers and bring up various assumptions about Korean drama content. The Korean drama adopted in this study is entitled The World of the Married. The drama that was broadcast by Trans TV a few months ago was very successful in anesthetizing the general public and making viewers adopt drama in their daily lives. This study aims to describe the female self-image of the main character, Ji Sun Woo’s in the Korean drama entitled The World of the Married which raises the issue of divorce and shows the value of feminism as shown by Ji Sun Woo as a strong figure and a brave female character who can make her own decisions to seek justice. By using qualitative research, data was collected using reading and note-taking techniques. The Korean drama The World of the Married discusses gender inequality, work, and social group problems and indirectly harms society as a whole, such as the social inequality on Lee Tae Oh's part between men and women in terms of leading and working..